The Role of Propaganda and Moral Disengagement Within Meat Industry Advertising. - Widolf, Helena Ellinor (Journal of Animal Ethics)
Advertising produced by the meat industry aims to stimulate positive feelings and thoughts about the exploitation of nonhuman animals. Propaganda techniques, such as glittering generalities, euphemism, virtue signaling, framing, and appealing to authority all comprise strategies used by this industry to convince consumers of the worthiness and appeal of its products. Mechanisms of moral disengagement, such as displacement of responsibility, normalization, and joke-making/humorization have also been detected within almost all varieties of meat industry advertising. Within this milieu, meat industry advocates appear to abandon all concern about marginalizing, disenfranchising, and disparaging animals.